Examining the Impact of Merger and Acquisition Perception on Customer Loyalty in the Banking Sector: Evidence from Structural Equation Modeling - Tuladhar, Anika; Devkota, Niranjan; Danuwar, Ranjana Kumari; Kayestha, Mijala; Dangol, Anuj Singh; Dhakal, Ajaya; Tiwari, Devi Raman; Timalsina, Dhurba Prasad; Koirala, Amita (Journal of Business and Management, 2024)
Background: A considerable number of studies in the Nepalese context have revealed that Nepal’s tourism sector has been adversely affected by the Covid-19 pandemic; however, none of these studies have quantified these consequences in monetary terms. This assessment is expected to offer valuable insight for enhancing the resilience of tourism sector to future global disruptions and developing tailored policies to bolster the Nepalese tourism sector against external shocks. Objectives: This study addresses a critical gap in understanding the full economic ramifications of the Covid-19 pandemic in the Nepalese tourism sector by quantifying the primary, secondary and tertiary revenue losses. By providing a comprehensive assessment of the pandemic’s impact, this study aims to inform policymakers and industry stakeholders in developing tailored strategies for recovery and resilience. Methods: Secondary data are used in this study. It employs Stynes et al.’s (2000) revised money generation framework and the Keynesian macroeconomic multiplier approach to assess the actual and expected economic impacts of tourism activities in Nepal during the pandemic periods of 2020 and 2021. The actual value is determined using the actual tourism statistics, while the expected value is based on the targeted tourism statistics reported by the Ministry of Culture, Tourism, and Civil Aviation, Nepal. The difference between the two estimates is attributed to the economic impact of the Covid-19 pandemic in those years. Results: This study reveals an expected revenue decrease of 1.038 billion US dollars in 2020 and 1.309 billion US dollars in 2021. In addition, the tourism multiplier values are declining in Nepal over the observed years. Conclusion: This study provides two key conclusions. First, the Nepalese tourism sector is susceptible to travel restrictions. Second, tourism revenue is being drained from the local economy due to the increasing importation of merchandise and services to satisfy the Nepalese tourism sector’s demand.